Karakteristik Hukum Islam Dalam Bidang Ekonomi - Ali Mutakin; Ghufron Maksum (Al Ashriyyah, 2019)
Al-Qur'an and Hadith are sources of Islamic law that have regulated all dimensions of human life, both those related to worship and mu'amalah. Islamic law which is associated with the original worship is regulated globally (mujmâl) in the Qur'an, then explained in detail by the Sunnah of the Prophet and formulated by jurists into fiqh books. Explanation of the Islamic Law related with mu'amalah is limited to the main points. Explanation of the Prophet, not as detailed as in his explanation of worship. Thus, mu'amalah has an open nature, so it is possible to develop through ijtihad by experts. While the characteristics of Islamic law, especially in muamalah, are perfect, universal, elastic, dynamic, flexible and not rigid, ta'aqquli and ta'abbudi, prioritizing substance rather than form, and creating benefit and not making it difficult. Islamic law is present on this earth, aiming to create benefit for all humanities, both in the world and the hereafter.